1985
DOI: 10.1111/j.1467-9906.1985.tb00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Staying Alive: Street Tree Survival in the Inner-City

Abstract: A study was conducted from 1978 to late 1984 of the survival of inner‐city street trees planted by the Oakland, California urban forestry program. The tree survival rate of approximately 60 to 70 percent from the trees planted in neighborhood parkways through urban forestry sponsored block parties contrasted sharply with less than one percent survival of trees planted earlier by the Model Cities program without community participation or ceremonial plantings. Explanations for the high tree survival were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…Mortality of urban trees varies greatly (see Roman (2006) for a review) and is influenced by a variety of factors. For example, Sklar and Ames (1985) report that community participation can significantly reduce tree mortality. In a study of urban trees in Baltimore, MD, USA, Nowak, Kuroda, and Crane (2004) found lowest mortality rates for low and medium density residential land and highest for transportation land use (2.2 and 20.2%, respectively).…”
Section: Tree Biomassmentioning
confidence: 97%
“…Mortality of urban trees varies greatly (see Roman (2006) for a review) and is influenced by a variety of factors. For example, Sklar and Ames (1985) report that community participation can significantly reduce tree mortality. In a study of urban trees in Baltimore, MD, USA, Nowak, Kuroda, and Crane (2004) found lowest mortality rates for low and medium density residential land and highest for transportation land use (2.2 and 20.2%, respectively).…”
Section: Tree Biomassmentioning
confidence: 97%
“…Urban tree mortality has been the subject of relatively few studies, but some studies of street trees in the temperate northeastern and western US and northern England have shown that mortality was related to tree condition, size, age, land use, water and nutrient stress, socio-economic status, community participation, and maintenance practices (Foster & Blaine, 1978;Gilbertson and Bradshaw, 1985;Nowak, McBride, & Beatty, 1990;Nowak et al, 2004;Sklar & Ames, 1985). For instance, Nowak et al (1990) observed an average morality of 19% for trees along boulevards in Oakland, California, with higher rates (34%) observed adjacent to apartments and public greenspaces.…”
Section: Introductionmentioning
confidence: 97%
“…Community outcomes flow from the social interactions that occur between participants of tree planting events that are held within their neighborhood (Bloniarz and Ryan 1997;Summit and Sommer 1997;Dwyer et al 2000;Westphal 2003;Elmendorf 2008). Community involvement in the planting and caring for trees can help to ensure the long-term survival of urban trees (Sklar and Ames 1985;Nowak et al 1990). Data collected during the 2005 trees census in New York City revealed that newly planted trees that exhibited visible signs of stewardship (i.e.…”
Section: Stakeholder Engagement In Urban Forestrymentioning
confidence: 99%